Ilgaz Dağı Milli Parkı nda Yer Alan Köylerin Kırsal Turizm Algısı - Çalışkan, Gürkan; Tanrısever, Canan; Mısırlı, irfan (Turk Turizm Arastirmalari Dergisi, 2021)
12 villages within the borders of Ilgaz Mountain National Park were determined as research area. The aim of the study is to evaluate the rural tourism potential of the villages located in Ilgaz Mountain National Park in terms of socio-cultural aspects. In this context, data were collected through focus group interviews with 12 village headmen in Ilgaz Mountain National Park, and the obtained data were analyzed and mapped with the MAXQDA program. As a result of the opinions of the headmen about the village people, it has been determined that the local people have a positive view on rural tourism, but the biggest constraints in the realization of rural tourism are financial support at local and national scale, vocational training and lack of employment.
Keywords: 15. Life on land; 12. Responsible consumption